2017
DOI: 10.21037/atm.2016.12.78
|View full text |Cite
|
Sign up to set email alerts
|

Effective implementation of novel MET pharmacodynamic assays in translational studies

Abstract: MET tyrosine kinase (TK) dysregulation is significantly implicated in many types of cancer. Despite over 20 years of drug development to target MET in cancers, a pure anti-MET therapeutic has not yet received market approval. The failure of two recently concluded phase III trials point to a major weakness in biomarker strategies to identify patients who will benefit most from MET therapies. The capability to interrogate oncogenic mutations in MET via circulating tumor DNA (ctDNA) provides an important advancem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…The statistical analysis was done on each VOC and EO composition. The principal component analysis (PCA) was performed selecting the two highest principal components (PCs) of a variance/covariance matrix, methods aimed at reducing the dimensionality of the multivariate data of the matrices, while preserving most of the variance [ 58 ]. The hierarchical cluster analysis (HCA) was performed using paired group (UPGMA) algorithm and Bray-Curtis as a similarity index for both the headspace analyses and the EO contents.…”
Section: Methodsmentioning
confidence: 99%
“…The statistical analysis was done on each VOC and EO composition. The principal component analysis (PCA) was performed selecting the two highest principal components (PCs) of a variance/covariance matrix, methods aimed at reducing the dimensionality of the multivariate data of the matrices, while preserving most of the variance [ 58 ]. The hierarchical cluster analysis (HCA) was performed using paired group (UPGMA) algorithm and Bray-Curtis as a similarity index for both the headspace analyses and the EO contents.…”
Section: Methodsmentioning
confidence: 99%
“…To illustrate the value of our novel EMT TF antibodies for examining tumor cell EMT in a complex histological context, we used these antibodies to assess EMT TF expression in a human HGF ( hHGF ) knock-in mouse xenograft model in which implanted human H596 non-small cell lung cancer (NSCLC) tumors undergo induction of EMT due to: 1) constitutive expression and secretion of hHGF by mouse stromal cells in the tumor microenvironment [ 11 ] and 2) potentiated activity of the human MET receptor in H596 tumors resulting from a MET exon 14−skipping mutation that suppresses MET proteasomal degradation [ 12 ]. Relative to H596 NSCLC tumors implanted in wild-type SCID mice, H596 tumors implanted in homozygous human HGF knock-in ( hHGF ki/ki ) mice exhibit enhanced growth rates and mesenchymal-like phenotypes, the latter assessed via immunofluorescence assays for E-cadherin and vimentin, markers of the epithelial and mesenchymal states, respectively [ 11 ]. We first confirmed that H596 tumor−bearing hHGF ki/ki mice exhibited substantially higher plasma hHGF levels compared to H596 tumor−bearing SCID mice, which had plasma hHGF levels below the lower limit of quantitation ( S4 Fig ).…”
Section: Resultsmentioning
confidence: 99%
“…In the latter case, we took advantage of the known role of HGF/Met signaling in inducing EMT [ 10 ] and compared EMT transcription factor (TF) expression in human non-small cell lung cancer (NSCLC) H596 tumors grown in severe combined immunodeficiency (SCID) mice to those implanted in SCID mice containing a homozygous human HGF ( hHGF ) knock-in mutation. hHGF knock-in H596 models exhibit rapid tumor growth and constitutive tumor EMT due to hHGF secretion by mouse stromal cells, thereby enhancing tumor HGF/MET signaling [ 11 ]; H596 tumors are particularly receptive to enhanced HGF secretion due to the presence of a MET exon 14−skipping mutation that suppresses proteasome-mediated MET degradation [ 12 ]. To validate the in vivo use of our antibody for the CSC marker CD133, we compared SUM149PT triple-negative breast cancer (TNBC) xenograft models treated with vehicle or the CSC-targeting focal adhesion kinase (FAK) inhibitor VS-6063 (defactinib; formerly PF-04554878) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the recent years, the use of vesicles as biological carriers has also been extended to cancer immunotherapy [ 18 ]. This kind of cancer treatment involves the use of extracellular vesicles to transport molecules capable of triggering an immune response to damage cancer cells.…”
Section: Extracellular Vesicles: An Introductionmentioning
confidence: 99%